A phase II study of DFP-14323, a non-specific immunomodulator, in combination with low-dose afatinib as first-line therapy for common EGFR mutation-positive NSCLC - Hiroshige Yoshioka; Masahide Mori; Nobuyuki Katakami; Toshihide Yokoyama; Hiroyasu Kaneda; Hirotaka Matsumoto; Motohiro Tamiya; Kouji Yamamoto; Cheng-long Huang (Therapeutic Advances in Medical Oncology, 2026)
Background Aminopeptidase N (CD13) has been reported to be a prognostic factor in non-small cell lung cancer (NSCLC). DFP-14323 (INN: ubenimex) is a CD13 inhibitor and a low-toxicity, non-specific immunomodulator approved in Japan for the maintenance treatment of adult acute non-lymphocytic leukemia. Objectives This study explored the potential immunomodulatory synergy of DFP-14323 with EGFR-TKIs in patients with advanced NSCLC. Design A prospective, multicenter, open-label, single-arm phase II study. Methods Stage III/IV treatment-naïve patients with activating EGFR mutation-positive (Ex19del/L858R) NSCLC were treated with 10 mg/day of DFP-14323 and a starting dose of 20 mg/day of afatinib, continued until disease progression or intolerable toxicity. The primary endpoint was the disease control rate (DCR). A total of 26 patients were enrolled based on Simon’s two-stage design (threshold DCR of 70%, expected DCR of 90%; two-sided α=0.05, β error=0.20). Results The DCR as primary endpoint was 100% (95% confidence interval (CI), 86.8–100.0%). Independent radiological review at 72 weeks demonstrated a median progression-free survival (PFS) of 16.6 months (95% CI, 10.2–22.9). Updated investigator-exploratory follow-up revealed a median PFS was 23.1 months (95% CI, 12.9– not estimable; median follow-up period: 22.6 months). One grade 3 paronychia was considered DFP-14323-related, while other adverse events were attributable to afatinib. No grade 4-5 adverse events occurred. Grade 1 interstitial lung disease occurred in one patient and resolved quickly. Conclusions The combination of DFP-14323 and low-dose afatinib was considered to have the potential for future clinical utility for EGFR mutation-positive NSCLC. As the next step, a study evaluating this combination therapy in uncommon EGFR mutation-positive NSCLC is currently underway in Japan (jRCT2061230111).